Search for point sources of ultra-high-energy photons with the Telescope Array surface detector. Issue 3 (3rd February 2020) - Abbasi, R U; Abe, M; Abu-Zayyad, T; Allen, M; Azuma, R; Barcikowski, E; Belz, J W; Bergman, D R; Blake, S A; Cady, R; Cheon, B G; Chiba, J; et al.
ABSTRACT: The surface detector (SD) of the Telescope Array (TA) experiment allows us to detect indirectly photons with energies of the order of 10 18 eV and higher, and to separate photons from the cosmic ray background. In this paper, we present the results of a blind search for point sources of ultra-high-energy (UHE) photons in the Northern sky using the TA SD data. The photon-induced extensive air showers are separated from the hadron-induced extensive air shower background by means of a multivariate classifier based upon 16 parameters that characterize the air shower events. No significant evidence for the photon point sources is found. The upper limits are set on the flux of photons from each particular direction in the sky within the TA field of view, according to the experiment's angular resolution for photons. The average 95 per cent confidence level upper-limits for the point-source flux of photons with energies greater than 10 18, 10 18.5, 10 19, 10 19.5 and 10 20 eV are 0.094, 0.029, 0.010, 0.0073 and 0.0058 km −2 yr −1, respectively. For energies higher than 10 18.5 eV, the photon point-source limits are set for the first time. Numerical results for each given direction in each energy range are provided as a supplement to this paper.